Health system resilience: An urgent need to mitigate the future unprecedented pandemic - Asniar, Asniar (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Health system resilience: An urgent need to mitigate the future unprecedented pandemic